Psychological Capital in Organizational Contexts: A Systematic Literature Review - Nia Riana; L. Rini Sugiarti; Fendy Suhariadi (Jurnal Ilmu Multidisiplin, 2026)
PsyCap is a key psychological asset to optimize employee performance and well-being during rapid organizational change and uncertainty. According to Positive Organizational Behavior, PsyCap consists of four state-like components, hope, efficacy, resilience, and optimism (HERO) that can be quantified and nurtured to support human potential progression. This systematic literature review was performed based on studies from Scopus, Web of Science, and ScienceDirect by synthesising 47 empirical and theoretical papers published from 2004 to 2025 by applying the PRISMA methodology. As results show, PsyCap has significant positive effects on employee engagement, job satisfaction, performance, organizational commitment, and psychological well-being and reduces stress and turnover intention. The antecedents of PsyCap development are leadership; organizational support; and learning culture. PsyCap training and coaching are an example of intervention in which available psychological resources seem to benefit significantly. PsyCap could be considered to be an adaptable and developable form of human capital that enhances organizational and personal growth and further research has to go beyond digital and cross-cultural environments as well as be carried to emerging economies in Indonesia in particular. Psychological Capital, Positive Organizational Behavior, Employee Well-being, Organizational Performance and Systematic Literature Review.